2016
DOI: 10.1055/s-0042-112221
|View full text |Cite
|
Sign up to set email alerts
|

LI-RADS-CEUS – Proposal for a Contrast-Enhanced Ultrasound Algorithm for the Diagnosis of Hepatocellular Carcinoma in High-Risk Populations

Abstract: To develop a contrast-enhanced ultrasound algorithm (LI-RADS-CEUS = liver imaging reporting and data system with contrast-enhanced ultrasound) for the diagnosis of hepatocellular carcinoma (HCC) in patients at risk. A CEUS algorithm (LI-RADS-CEUS) was designed analogously to CT- and MRI-based LI-RADS. LI-RADS-CEUS was evaluated retrospectively in 50 patients at risk with confirmed HCC or non-HCC lesions (test group) with subsequent validation in a prospective cohort of 50 patients (validation group). Results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Furthermore, CEUS is recommended for the diagnostic workup of patients with colorectal cancer [32]. Similar to the reporting standards of MRI and CT, a reporting algorithm for CEUS has been established, LI-RADS CEUS, which ought to be used for standardized reporting in liver lesions for patients at risk of HCC [33]. So far, only a few studies have evaluated CEUS as a first-line diagnostic tool in the characterization of FLLs compared to MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CEUS is recommended for the diagnostic workup of patients with colorectal cancer [32]. Similar to the reporting standards of MRI and CT, a reporting algorithm for CEUS has been established, LI-RADS CEUS, which ought to be used for standardized reporting in liver lesions for patients at risk of HCC [33]. So far, only a few studies have evaluated CEUS as a first-line diagnostic tool in the characterization of FLLs compared to MRI.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Doppler and contrast-enhanced ultrasound help in the characterisation of FLL. [5][6][7][8][9] Nonetheless, a proportion of up to 30%-40% remain undetermined, so requiring cross-sectional imaging assessment and/or biopsy. Therefore, simple methods allowing to refine FLL characterisation in real-time on US are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Different perfusion patterns have been reported for ICC. For the arterial phase, four perfusion patterns were seen in the literature, including peripheral rim-like hyper-enhancement (50%), heterogeneous hyper-enhancement (24%), heterogeneous hypo-enhancement (20%), and homogeneous hyper-enhancement (6%) (5,6,8). These differences in arterial phase enhancement may be due to the amount of tumor cells and the fiber distribution within the lesions (6).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time CEUS has been widely used in the diagnosis of hepatic space-occupying lesions (7,8). It has been reported that ICCs showed different perfusion characters during CEUS (4,9-11).…”
Section: Introductionmentioning
confidence: 99%